2020
DOI: 10.1016/j.ihj.2020.07.018
|View full text |Cite
|
Sign up to set email alerts
|

National interventional council data for the year 2018-India

Abstract: Objective The National interventional Council of Cardiological Society of India (CSI–NIC) is the society representing all the practising interventional cardiologists across country. Every year National interventional council collects the data of coronary and non-coronary interventions across all the cath labs in the country and data will be presented at annual meet. This Data will show the burden of disease, number of interventions and adaption of various newer procedures from various centers acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…from 0.32% in 2013 and 1.16% in 2017 the proportion has gone rapidly up to 4.22% in 2018. 12 The low use of IVUS may be due to limited availability, added cost, and increased procedure time. Therefore, alternatively the straight–line equation derived by us between IVUS and QCA could help predict the IVUS diameter or the so-called true vessel size from QCA measurement in the absence of IVUS performance.…”
Section: Discussionmentioning
confidence: 99%
“…from 0.32% in 2013 and 1.16% in 2017 the proportion has gone rapidly up to 4.22% in 2018. 12 The low use of IVUS may be due to limited availability, added cost, and increased procedure time. Therefore, alternatively the straight–line equation derived by us between IVUS and QCA could help predict the IVUS diameter or the so-called true vessel size from QCA measurement in the absence of IVUS performance.…”
Section: Discussionmentioning
confidence: 99%
“…In the coronary interventional registry of Indian patients undergoing coronary angiography and percutaneous coronary intervention in 2011, out of 193,728 stents used, nearly 30% of stents were deployed in the setting of multivessel CAD 11 . In corroboration with this, cross-sectional data from the National Interventional Council in 2018 also noted a rise in the rate of complex coronary interventions, with more patients undergoing left main and multivessel PCI in 2018, as compared to previous years 12 . Interestingly, similar observations have been noted amongst South Asians undergoing angiography in the United States, who have been found to have smaller coronary luminal diameters, higher-grade coronary artery obstructions and a higher prevalence of multivessel disease [13][14][15] .…”
Section: Patterns Of Cardiovascular Disease In Indiamentioning
confidence: 71%
“…Data from the National Interventional Council show that there is a trend towards increasing primary PCI in India in recent years for the treatment of STEMI. The overall percentage of primary PCI remains insignificant, however, when the total STEMI burden of the country is considered 8 . The recent STREAM (STrategic Reperfusion Early After Myocardial infarction) data 6 and the Indian data from the STEP-PAMI study 5 showed that the PI strategy compared well with primary PCI in overall morbidity and mortality.…”
Section: Developing a System Of Care For Stemimentioning
confidence: 99%